The correct answer is:
A) A 90° counterclockwise rotation about the origin followed by a reflection across the y-axis.
Explanation:
We will represent the transformations algebraically.
For A:
A 90° rotation counterclockwise maps
(x,y)→(-y,x).
A reflection across the y-axis negates the x-coordinate; this maps our new point
(-y,x)→(y,x).
If we reverse these and reflect across the y-axis first, negating the x-coordinate, we map
(x,y)→(-x,y).
Rotating this 90° counterclockwise, we reverse the x- and y-coordinates and negate the new x:
(-x,y)→(-y,-x).
Since these are different end coordinates, this is the correct answer.